Organoleptic quality of reduced fat turkey sausage using pea fiber or potato starch additives - Vargáné Visi, Éva; Toxanbayeva, Botagoz; Andrássyné Baka, Gabriella; Romvári, Róbert (Acta Agraria Kaposváriensis, 2017)
Reduced fat Bologna-type turkey sausages were manufactured and the effects of pea fiber or potato starch based fat replacers on organoleptic characteristics were evaluated. Fat was partially (25, 50 or 75 %) replaced with potato starch or pea fiber resulting 16-17%, 31-33% and 45-50% decrease in gross energy content, respectively. Differences in measured color values were small, being undetectable by assessors. Reduced fat sausages containing medium or high levels of potato starch (3.9%, 5.8%) or high level of pea fiber (1.8%) were perceived less salty than control and scores of saltiness were in line with that of juiciness. Organoleptic properties of sausages with low and medium levels of pea fiber (0.6, 1.2%) and potato starch (1.9%) were similar than that of full fat sausage.
Keywords: fat replacer; Bologna sausage; turkey; saltiness; juiciness